The Impact of Using “STEM” Method in Improving the Gifted Learners of the Intermediate Level’s Abilities in schools at Tulkarm and Qalqilya governorates in Problem Solving - Eid, Abdullah Fathi; Qasem, Loway Hashem; Abu Saa, Jafar Wasfi (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to investigate the impact of using “STEM” Method in improving the gifted learners of the intermediate level’s abilities in problem solving. “STEM” is considered among the methods that blend science, mathematics, technology, and engineering, where the learner is the center of the learning process, in addition to being a problem solving- centered method. A set of problems that require knowledge and skills related to the scientific, technological, and engineering content were chosen to be solved. For the sake of the study, a test was constructed in order to reveal the ability in problem solving, and consisted of 10 open-ended problems. The study also used the semi experimental method that depends on designing a sole group and (a pre-test and a post-test). The sample of the study consisted of (60) learners of the intermediate level that are chosen intentionally. The test of problem solving was applied before and after the experiment, after assuring its reliability and stability. The findings of the study assured the effectiveness of teaching and learning according to “STEM” Method in order to enhance the learners of the intermediate level’s abilities in problem solving. The research recommended the use of the STEM approach in integrating science, mathematics and technology in the Palestinian curricula, and working on designing enrichment units in which the merger between previous branches of science is achieved and distributed to schools. The research also recommended preparing intensive training courses for teachers in designing and implementing educational units according to the STEM approach, and providing them with the necessary knowledge and skills to achieve the goals of using the STEM curriculum in education.
Keywords: “STEM”; The Blended Courses; Problem Solving; The Gifted Learners of the Intermediate Level